An Android-based Career Information to Improve The Career Choice of Vocational High Schools Students - Lacksana, Indra; Sugiyo, Sugiyo; Awalya, Awalya (Jurnal Bimbingan Konseling, 2018)
The objective of this study was to improve students’ career choice by using an android medium in the form of career information. To purse such objective, this study used one-group pretest-posttest research design. For more, the instrument used in data collection was career choice scale. This instrument was given to 36 tenth grade students as the research subjects taken from 300 students selected by using purposive random sampling technique. After the data were analyzed, the research findings showed that there was an increase in score as many as 29.92 after using the android application on students’ career choice. At last, this study confirms that an android-based career information application can improve career choice.